Evaluation The effect of external cooling and vibration on pain during local anesthetic injection - احمد لبانه; عبد الوهاب نور الله (Latakia University Journal -Medical Sciences Series, 2024)
Objective: Comparison the efficacy of external cooling and vibration in reducing pain associated with local anesthetic injection with the conventional infiltration technique. Materials and methods: this randomized split-mouth clinical study included 17 children, aged between 6_12 years. Each child received a conventional infiltration injection on one side, and the second was on the opposite side of the same jaw with the application of external cold and vibration, over two sessions, randomly. At the end of the session, pain was subjectively assessed using the Wong_Baker_Faces pain scale (WBFPS). Results: The use of External Cooling and Vibration showed less pain during local anesthetic compared to conventional infiltration injection,but was not statistically significant ( p-value>0.05). Conclusion: Application of external cooling and vibration can reduce pain during infiltration injection of local anesthetic.